Promoting Excellence in Turkey's Schools - World Bank (Washington, DC, 2013)
The education system in Turkey has shown remarkable improvement since 2003 in terms of better student performance and reduced inequality with a concurrent and sustained increase in enrollments. The expansion of primary and secondary schooling was accompanied by the development of new curriculum in primary and secondary education, especially since 2004. A recent independent assessment of the revised secondary school curriculum regarded it as an improvement over the curriculum used in the past. Curriculum reform was accompanied by initiatives to improve the teaching profession policies. This report finds that most of the progress in the education system since 2003 has been the result of a combination of the overall socioeconomic progress being made in Turkey and increased effectiveness in the delivery of education. The Government's educational policies have contributed to the improvements in education outcomes including curriculum reform, phased modernization of teaching and learning materials and practices, stronger focus on measuring learning outcomes through large scale national and international assessments, and enhanced monitoring and evaluation systems. This report continues the work undertaken in the previous World Bank (2011) report which examined a cross section of countries that participated in Program for International Student Assessment (PISA) 2009, and pointed out that the average 15 year old in Turkey is school year behind the average Organization for Economic Cooperation and Development (OECD) counterpart in reading, math, and science skills. This report will analyze the evolution of regional and income inequalities in PISA scores, the overall effectiveness of the delivery of education in Turkey, and identify areas on which policymakers can focus to further improve educational outcomes. The report pays particular attention to the role played by improved teaching and greater school accountability in improving educational outcomes.